A RhoA signaling pathway regulates dendritic Golgi outpost formation - Quassollo Infanzon, Gonzalo Emiliano (2015)
Summary The neuronal Golgi apparatus (GA) localizes to the perinuclear region and dendrites as tubulo-vesicular structures designated Golgi outposts (GOPs). Current evidence suggests that GOPs shape dendrite morphology and serve as platforms for the local delivery of synaptic receptors. However, the mechanisms underlying GOP formation remain a mystery. Using live-cell imaging and confocal microscopy in cultured hippocampal neurons, we now show that GOPs destined to major "apical" dendrites are generated from the somatic GA by a sequence of events involving: (1) generation of a GA-derived tubule; (2) tubule elongation and deployment into the dendrite; (3) tubule fission; and (4) transport and condensation of the fissioned tubule. A RhoA-Rock signaling pathway involving LIMK1, PKD1, slingshot, cofilin, and dynamin regulates polarized GOP formation by controlling the tubule fission. Our observations identify a mechanism underlying polarized GOP biogenesis and provide new insights regarding involvement of RhoA in dendritic development and polarization.